Consumer Perspectives of Safewards Impact in Acute Inpatient Mental Health Wards in Victoria, Australia - Fletcher, Justine; Buchanan-Hagen, Sally; Brophy, Lisa; Kinner, Stuart A.; Hamilton, Bridget (Frontiers in Psychiatry, 2019)
Background: Inpatient mental health wards are reported by many consumers to be custodial, unsafe, and lacking in therapeutic relationships. These consumer experiences are concerning, given international policy directives requiring recovery-oriented practice. Safewards is both a model and a suite of interventions designed to improve safety for consumers and staff. Positive results in reducing seclusion have been reported. However, the voice of consumers has been absent from the literature regarding Safewards in practice. Aim: To describe the impact of Safewards on consumer experiences of inpatient mental health services. Method: A post-intervention survey was conducted with 72 consumers on 10 inpatient mental health wards, 9-12 months after Safewards was implemented. Results: Quantitative data showed that participants felt more positive about their experience of an inpatient unit, safer, and more connected with nursing staff. Participants reported that the impact of verbal and physical aggression had reduced because of Safewards. Qualitatively, participants reported increased respect, hope, sense of community, and safety, and reduced feelings of isolation. Some participants raised concerns about the language and intention of some interventions being condescending. Discussion: Consumers’ responses to Safewards were positive, highlighting numerous improvements of importance to consumers since its implementation across a range of ward types. The findings suggest that Safewards offers a pathway to reducing restrictive interventions and enables a move towards recovery-oriented practice.